The relationship between psychological frequency and the accuracy of football handling skills. (Journal of the College of Basic Education, 2025)
The research aims to: identify the relationship between psychological frequency and skill accuracy. With football. The researcher objected that there is a correlation between psychological hesitation and the skill of transferring in football, and the researcher chose the research complex represented by the Haifa Sports Club (one hundred advanced players) and their number is (29) not out of love, as the researcher used (20) players representing the research sample and they were chosen randomly representing (68%) of the original community, and excluded (7) players representing the exploratory experiment) and excluded (2) players who are goalkeepers. The research The researcher used the psychological frequency scale (Frans Hussein (2005) and a special test for the accuracy of the handling skill that was determined by experts in order to identify the nature of the correlation between the research variables after extracting the results through the statistical package SPSS. The researcher concluded that there is a significant correlation between the psychological frequency and the accuracy of the handling skill in football.